Fine Structure of the Motile Cells and Flagella in a Member of the Actinoplanaceae (Actinomycetales) - Bland, Charles E. (1970)
The motile cells (sporangiospores) of an undescribed member of the Actinoplanaceae are studied by electron microscopy as shadowed, negatively stained, and sectioned preparations. The rod-shaped spores exhibit a typically bacterial internal structure. However, a single tubular structure (rhapidosome) is positioned just inside the site of flagellar attachment of each spore and is oriented perpendicular to the direction of the flagella. Flagella arise from basal dises and pass through the plasma membrane and the two-layered cell wall to become associated with other flagella to function as a posteriorly directed unit. Each flagellum consists of a helical band or ribbon which dissociates into 5 or 6 subfibrils.